1996
DOI: 10.1182/blood.v88.9.3482.bloodjournal8893482
|View full text |Cite
|
Sign up to set email alerts
|

Pyrrolidine dithiocarbamate inhibits the production of interleukin-6, interleukin-8, and granulocyte-macrophage colony-stimulating factor by human endothelial cells in response to inflammatory mediators: modulation of NF-kappa B and AP-1 transcription factors activity

Abstract: Endothelial cells (EC) play a key role in the inflammatory response, both by the production of proinflammatory cytokines and by their interaction with leukocytes. Molecular genetic analysis has demonstrated that functional NF-kappa B sites are involved in the transcription of interleukin-6 (IL-6), IL-8, and granulocyte-macrophage colony-stimulating factor (GM-CSF) genes in response to inflammatory mediators. Thus, we have explored the effect of two inhibitors of the NF-kappa B activation, pyrrolidine dithiocar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
38
0

Year Published

1999
1999
2015
2015

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 160 publications
(41 citation statements)
references
References 43 publications
3
38
0
Order By: Relevance
“…We found that PDTC strongly inhibits the in vivo activation of NF-O B in lung and liver of LPS-challenged mice. A number of antioxidants, including PDTC, efficiently inhibit NF-O B activation induced by TNF- § or LPS in a number of cell systems [13,20,23,24]. These effects appear to be mediated by the powerful radical scavenger properties of this antioxidant, which apparently counteracts ROI signaling generated by NF-O B activators [18,23,25].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We found that PDTC strongly inhibits the in vivo activation of NF-O B in lung and liver of LPS-challenged mice. A number of antioxidants, including PDTC, efficiently inhibit NF-O B activation induced by TNF- § or LPS in a number of cell systems [13,20,23,24]. These effects appear to be mediated by the powerful radical scavenger properties of this antioxidant, which apparently counteracts ROI signaling generated by NF-O B activators [18,23,25].…”
Section: Discussionmentioning
confidence: 99%
“…Despite these considerations, mice protected from LPS-or TNF- § -induced septic shock remain alive for months after LPS challenge, and no differences were observed with respect to untreated control mice during this time. In addition, PDTC activates the transcription factors AP-1 and C/EBP g [18,24,43,44]. Whereas the PDTCmediated activation of C/EBP g appears to account for important beneficial effects in colon cancer therapy, enhancing the cytotoxic efficacy of the conventional anti-tumoral drugs such as 5-fluouracil and doxorubicin [43], the effects of PDTC activating AP-1 in a number of cells types have not been evaluated in vivo.…”
Section: Discussionmentioning
confidence: 99%
“…As an important pro‐inflammatory chemokine, IL‐8 is one of the well‐established target genes for NF‐κB and synthesized by many different cell types including bronchial epithelium after stimulated by bacterial, viral products or chemicals . To further confirm scratch injury can induce inflammatory responses in BECs, IL‐8 was examined by ELISA and real‐time PCR.…”
Section: Resultsmentioning
confidence: 99%
“…On cellular stimulation, IκBα is rapidly ubiquitinated and degraded through the 26S proteasome pathway and exposed the nuclear localization sequence of NF‐κB, which allows NF‐κB entering the nucleus . Activation of NF‐κB could enhance the expression of genes encoding inflammatory cytokines, such as IL‐8 . It is the core of inflammatory reactions, closely related to cellular stimulation such as LPS and scratch‐induced inflammation .…”
mentioning
confidence: 99%
See 1 more Smart Citation